Transforming Alzheimer's Treatment: Unveiling New Potential with Drug Repurposing Strategies - Mishra, Ashish Sriram; Vasanthan, Manimaran; Ghosh, Bhavna; Sivakumar, Ponnurengam Malliappan (Current Medicinal Chemistry, 2025)
Alzheimer's disease (AD) remains a significant challenge in neurology, marked by progressive cognitive decline and neurodegeneration. Despite extensive research efforts, effective treatments are still lacking. Traditional drug discovery is often slow and costly, frequently resulting in limited success. Drug repurposing, which identifies new therapeutic uses for existing medications, has emerged as a promising approach to expedite AD treatment development. This review examines the potential of drug repurposing to transform AD therapy by utilizing the established safety profiles and known mechanisms of current drugs. We explore various repurposed drugs under investigation for AD, originally intended for cardiovascular, metabolic, and psychiatric conditions. Detailed discussions include how these drugs provide neuroprotective benefits by inhibiting amyloid-beta aggregation, reducing tau phosphorylation, and modulating neuroinflammation. Additionally, we emphasize the benefits of drug repurposing, such as shortened development timelines, lower costs, and increased chances of clinical success. By integrating current research findings, this review offers a thorough overview of the most promising repurposed drug candidates and their potential impact on AD treatment strategies. It stresses the importance of innovative approaches in AD research and calls for greater investment in drug repurposing initiatives. Through these strategies, we aim to accelerate the availability of effective treatments, providing renewed hope and a brighter future for those affected by this devastating disease.
Keywords: neuroinflammation